2003
DOI: 10.1038/sj.bjc.6601311
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant and neoadjuvant therapy for gastric cancer using epirubicin/cisplatin/5-fluorouracil (ECF) and alternative regimens before and after chemoradiation

Abstract: Chemoradiation is now used more commonly for gastric cancer following publication of the US Intergroup trial results that demonstrate an advantage to adjuvant postoperative chemoradiotherapy. However, there remain concerns regarding the toxicity of this treatment, the optimal chemotherapy regimen and the optimal method of radiotherapy delivery. In this prospective study, we evaluated the toxicity and feasibility of an alternative chemoradiation regimen to that used in the Intergroup trial. A total of 26 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…In addition, improved radiation techniques, in particular the use of 3D radiation treatment planning resulting in four or more field techniques in the majority of patients compared with simple AP-PA portals in the INT 0116 trial, and the application of 5-FU as continuous infusion during radiotherapy as well as improved supportive measures, may all have contributed to the apparently better tolerability. Similar conclusions have been drawn by other recent studies [26,27]. Weight loss and anorexia represent particular problems in this patient group.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, improved radiation techniques, in particular the use of 3D radiation treatment planning resulting in four or more field techniques in the majority of patients compared with simple AP-PA portals in the INT 0116 trial, and the application of 5-FU as continuous infusion during radiotherapy as well as improved supportive measures, may all have contributed to the apparently better tolerability. Similar conclusions have been drawn by other recent studies [26,27]. Weight loss and anorexia represent particular problems in this patient group.…”
Section: Discussionsupporting
confidence: 92%
“…CTX 90 -92 3 100 -60 Therefore, with the use of more eVective chemotherapy regimens than bolus 5-FU/leucovorin according to the Mayo-protocol, which was used in the US Intergroup Study, the eYcacy of adjuvant chemoradiotherapy might be improved. Leong et al 2003 demonstrated feasibility and tolerability of a combination chemotherapy in the adjuvant setting after completely resected gastric cancer, applying one cycle of combination chemotherapy of epirubicin, cisplatin and 5-FU each before and after chemoradiation in 26 patients with an acceptable toxicity proWle (Leong et al 2003). Recently, these results were conWrmed by a pilot study of Lee et al, who evaluated a combination regimen of 5-FU and cisplatin before and after chemoradiation including capecitabine.…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, postoperative fluorouracil-based CT-RT is the recommended standard of care for pT3 and Nϩ gastric cancers in the United States, 9 and several phase 2 studies exploring substitution of bolus fluorouracil with the better-tolerated continuous infusion of fluorouracil and the addition of cisplatin or paclitaxel as a second drug were recently published. [10][11][12] Overall, all of these studies were characterized by difficulty in completing the planned treatment in more than 80% of patients. However, CT-RT is not considered the standard of care in Europe for patients with radically resected gastric cancer.…”
mentioning
confidence: 99%